Car seat cover supply chain investigation in a small town in Brazil (Research, Society and Development, 2022)
With the current pandemic scenario, enterprises have been innovating more and more and looking for an alternative way to maintain themselves and generate jobs. In this context arrived the Gig Economy, which allows people to undertake and open their businesses, and with the possibility of taking their business to the digital side, that is, using digital platforms to sell their products, such as the Mercado Libre, among other platforms. In the city of Campo do Meio/MG, a small town in Brazil, many people lost their jobs, and with that came the need to innovate. As a result, this city represents more than 80% of Brazil's entire market supplier of car seat covers in one of the biggest online platforms. However, with the significant increase in demand and supply, companies may have some problems with their supply chain. We surveyed the car seat covers company in the city to collect accurate and detailed information on the functioning of their supply chain. We noticed that companies had difficulties implementing digital platforms due to the lack of training of the workforce. Moreover, even some companies that already worked with some digital resources, such as websites or online stores, still had this difficulty, as not every workforce knew how these resources worked. Therefore, among other results, this research observed a tremendous demand for innovation and adaptation regarding the digital market.